Examining Authorship Dynamics, Publication Patterns, and Affiliations in the Pakistan Journal of Medical and Health Sciences (PJMHS) from 2009-2019 - Zameer Hussain Baladi, Ghulam Farid, Ayesha Gulzar, Manzoor Hussain, Sadaf Iftikhar, Maryam Naz, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: The Pakistan Journal of Medical and Health Sciences have been peer-reviewed and is included in the Scopus-Elsevier database. This study represents (PJMHS)'s contribution to research productivity from 2019 to 2009. Methods and Materials: The published data records were obtained from the PJMHS website and the Scopus-Elsevier database for MS Office Excel Sheet tabulation. The frequency of publications, the type of papers, the use of pages, citations, and the initial author's affiliation with their country. Results: In 43 issues, 15401 (4%) authors wrote 3817 items in seven categories. The average number of pages consumed was (2.8%), with 896 (23.4%) citations in publications. The collaboration of three authors provided 1339 (36.6%) papers and received the top spot, while four authors, 3344 (21.7%), contributed 836 (22%). The first authors from 29 nations engaged in publications, with Pakistan leading the way with 3484 (91%), Iran second with 79 (2%), Indonesia third with 77 (2%), and the Kingdom of Saudi Arabia fourth with 65 (1.7%). Practical Implication: The information assess the influence and relevance of the research published in the Pakistan Journal of Medical and Health Sciences. In nut-shell, the published data empowers readers to stay informed about the journal's publication trends, authorship patterns, and the breadth of content available. It enables researchers to identify potential collaborators, explore different document types, and gauge the impact of published articles through citation analysis. Conclusion: Pakistan Journal of Medical and Health Sciences (PJMHS) is a peer-reviewed journal that is published continuously and assists medical and health sciences research communities in gaining their attention in sharing ideas on a reciprocal basis from similar specialties or sub-specialties of common disciplines Keywords: Bibliometric, Pakistan Journal of Medical and Health Sciences, Pakistan, medical education and research, bibliometric, Zameer Baladi.